Simulasi Mesin Induksi Tanpa Sensor Kecepatan Menggunakan Pengendali Orientasi Vektor - Feri Yusivar; Nanda Avianto Wicaksono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
This research is intended to develop a speed sensorless induction machine model of wind turbine applications using vector orientation control method. This research is expected to use the results of previous research in induction motor applications, such as the development of adaptive vector control of sensorless induction motor for estimating the actual speed. The system in this paper consists of a wind turbine mechanical model, an induction machine model, and a vector orientation controller. The system is developed in S-Function C-MEX programs, and simulated using the MATLAB/Simulink. The system is tested in the condition that the wind speed and the reference rotor speed varies as step function. The results of the simulation show that the vector orientation controller is able to maintain the actual speed according to its reference, and the observer is able to estimate the actual rotor speed.